The Basic Financial Accounting Knowledge: A Panacea for Successful Entrepreneurship Study, among Postgraduate Students in the University of Ibadan - James, Aruleba Tomisin (American Journal of Creative Education, 2019)
Entrepreneurship education has the edict to furnish the youth with useful and practical knowledge, Skills (Guatam and Singh, 2015) and focusing on potentials (financial skill, business knowledge, career exploration, community awareness, good relationship and education) that will increase business and entrepreneurial potentials in other to shape up their disposition, philosophy and perception. The financial skill is what the majority of the current students is lacking due to educational background, as the centre is still admitting graduates of different disciples hence, depleting their managerial, academic and entrepreneurial strength. The paper objectives are to; examine the importance of financial accounting knowledge to the entrepreneurial pursuit of the students. Ascertain the effect of financial accounting knowledge on entrepreneurial activities of students at the Centre. And to assess the student’s level of interest in making financial accounting as a required course. The population consists of the second, third and fourth set students of Centre for Entrepreneurship and Innovation, with 112 as sample size. The instrument was administered via Whatsapp groups and physical distribution. The results revealed that there is a significant relationship between the two hypotheses. It insinuates that financial accounting is important to the entrepreneurial pursuit of the students. Knowledge of financial accounting to be acquired will impact and improve the entrepreneurial activities of students together with other potential skills they have been exposed to. Lastly, the students were firm on making financial accounting a required/compulsory course i.e level of interest in making financial accounting and related courses is high.